Carl Sagan : una vida en el cosmos - Poundstone, William (Biografías (Akal Editor), 2017)
A biography of twentieth-century scientist Carl Sagan, discussing his lifelong obsession with interplanetary travel and life in outer space, and considering how that interest made him an icon of popular culture, but reflected badly on his professional standing.